Properties of the Glucose-6-Phosphate Transporter from Chlamydia pneumoniae (HPTcp) and the Glucose-6-Phosphate Sensor from Escherichia coli (UhpC) - Schwöppe, Christian (American Society for Microbiology, 2002)

(untitled)
The amino acid sequence of the proposed glucose-6-phosphate (Glc6P) transporter from Chlamydia pneumoniae (HPTcp; hexose phosphate transporter [Chlamydia pneumoniae]) exhibits a higher degree of similarity to the Escherichia coli Glc6P sensor (UhpC) than to the E. coli Glc6P transporter (UhpT). Overexpression of His-UhpC in a UhpT-deficient E. coli strain revealed that the sensor protein is also able to transport Glc6P and exhibits an apparent K(m) ((Glc6P)) of 25 μM, whereas His-HPTcp exhibits an apparent K(m)( (Glc6P)) of 98 μM. His-HPTcp showed a four-times-lower specific activity than His-UhpT but a 56-times-higher specific activity than His-UhpC. Like His-UhpT and His-UhpC, the carrier His-HPTcp performs a sugar-phosphate/inorganic-phosphate antiporter mode of transport. Surprisingly, while physiological concentrations of inorganic phosphate competitively inhibited transport mediated by the E. coli proteins His-UhpT and His-UhpC, transport mediated by His-HPTcp was not inhibited. Interestingly, C(3)-organophosphates stimulated His-HPTcp activity but not His-UhpT- or His-UhpC-catalyzed Glc6P transport. In contrast to His-UhpC, the His-HPTcp protein does not act as a Glc6P sensor in the uhp regulon.